2021
DOI: 10.1177/02692163211013248
|View full text |Cite
|
Sign up to set email alerts
|

Emotional disclosure in palliative care: A scoping review of intervention characteristics and implementation factors

Abstract: Background: Emotional disclosure is the therapeutic expression of emotion. It holds potential as a means of providing psychological support. However, evidence of its efficacy in palliative settings is mixed. This may be due to variation in intervention characteristics. Aim: To derive a greater understanding of the characteristics of potentially effective emotional disclosure-based interventions in palliative care by: (1) Developing a taxonomy of emotional disclosure-based interventions tested in people with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Whilst Hawker and colleagues 29 did not indicate how total scores could be interpreted, previous systematic reviews using this tool classified studies with a total score of 18 and below, 18–30 and 31–36 as of poor, fair or good quality, respectively. 33 , 34 Studies were not excluded based on their quality, but they were reported to allow for a comprehensive understanding of the included studies and the data reported. It also helps to identify and pertinent problematic areas for future research.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst Hawker and colleagues 29 did not indicate how total scores could be interpreted, previous systematic reviews using this tool classified studies with a total score of 18 and below, 18–30 and 31–36 as of poor, fair or good quality, respectively. 33 , 34 Studies were not excluded based on their quality, but they were reported to allow for a comprehensive understanding of the included studies and the data reported. It also helps to identify and pertinent problematic areas for future research.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, holistic nursing has received increasing attention. In the current nursing system, psychological nursing has become an indispensable link in basic nursing, particularly in the context of emotional nursing[ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%